The Influence of Age on Visual Acuity in Postoperative Senile Cataract Patients Undergoing Phacoemulsification at Klinik Mata Dr. Imam - Renata Shafira Nanda; Imam Masduki; Elvina Prisila (Ahmad Dahlan Medical Journal, 2023)
Cataracts caused by aging are called senile cataracts. Phacoemulsification is the gold standard surgical method for cataract therapy. Postoperative visual acuity can be influenced by age. The objective of this study is to determine the characteristics of visual acuity and the influence of age on visual acuity in postoperative senile cataract patients undergoing phacoemulsification at Klinik Mata Dr. Imam. This study is retrospective research with a cross-sectional design. The data collected are secondary data from medical records, with a total of 106 respondents. The results of the univariate analysis showed that the majority of senile cataract patients undergoing phacoemulsification were in the elderly age group (55-65 years) with 42 cases (39.6%), male patients with 56 cases (52.8%), and 61 cases (57.5%) underwent surgery on the right eye. The best-corrected visual acuity in postoperative senile cataract patients undergoing phacoemulsification at Klinik Mata Dr. Imam was found on the 21st day. The largest proportion of patients achieving best-corrected visual acuity that meets the good standard set by WHO (6/6 - 6/18) was in the elderly age group (55-65 years) with 39 cases (41.5%), male patients with 50 cases (53.2%), and surgeries on the right eye with 52 cases (55.3%). Bivariate analysis was performed using the chi-square test and showed a significant influence between age and visual acuity in postoperative senile cataract patients undergoing phacoemulsification (p-value = 0.011). In conclusion, there is a significant influence of age on visual acuity in postoperative senile cataract patients undergoing phacoemulsification..